The Influence of Learning Models and Student Learning Activities on Collaboration Skills and Student Learning Outcomes - Telaumbanua, Debi M N; Syafriani, Dewi (UNDIKMA, 2024)
This research was conducted to determine whether or not there are differences in the value of collaboration skills and student learning outcomes taught using various learning models and student learning activities with the help of Macromedia Flash media on chemical bonding material, as well as to see the interaction between learning models and student learning activities on collaboration skills and student learning outcomes. Experimental class I (X-6) applied the Discovery Learning model and experimental class II (X-10) applied the Guided Inquiry model. The instrument used is a test instrument, a non-test instrument. Hypothesis testing was carried out using two-way ANOVA with multivariate General Linear Model (GLM). The research results obtained a price of sig. 0.000 for collaboration skill value and sig price. 0.001 for learning outcomes. Price sig. < ???? (0.05) so there is a significant difference in the average value of collaboration skills and student learning outcomes with various learning models. Obtained sig value. 0.000 on collaboration skills and learning outcomes. Sig price value. < ???? (0.05) so there is a significant difference in the average value of collaboration skills and student learning outcomes with various learning activities. The interaction between the learning model and learning activities obtained a sig value. 0.045 for collaboration skills and sig. 0.014 for learning outcomes. From the two sig values. < ???? (0.05) so that Ha is accepted and Ho is rejected, there is an interaction between the learning model and student learning activities on the value of collaboration skills and student learning outcomes in the Chemical Bond material.